2020
DOI: 10.1111/bjhp.12453
|View full text |Cite
|
Sign up to set email alerts
|

Understanding face mask use to prevent coronavirus and other illnesses: Development of a multidimensional face mask perceptions scale

Abstract: Face masks are an avenue to curb the spread of coronavirus, but few people in Western societies wear face masks. Social scientists have rarely studied face mask wearing, leaving little guidance for methods to encourage these behaviours. In the current article, we provide an approach to address this issue by developing the 32-item and 8-dimension Face Mask Perceptions Scale (FMPS). We begin by developing an over-representative item list in a qualitative study, wherein participants' responses are used to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 24 publications
7
109
1
1
Order By: Relevance
“…These findings suggest there exists a distinct set of negative attitudes that are not simply the absence of positive attitudes [ 40 ]. A recent study describing attitudes toward mask use similarly identified separate factors related to perceived health benefits and personal freedom [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest there exists a distinct set of negative attitudes that are not simply the absence of positive attitudes [ 40 ]. A recent study describing attitudes toward mask use similarly identified separate factors related to perceived health benefits and personal freedom [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, we have published 17 COVID-19 papers (Bacon & Corr, 2020;Gibson Miller et al, 2020;Grover, McClelland, & Furnham, 2020;Horesh, Kapel Lev-Ari, & Hasson-Ohayon, 2020;Howard, 2020;Lades, Laffan, Daly, & Delaney, 2020;Lauri Korajlija & Jokic-Begic, 2020;Lin et al, 2020;Marinthe, Brown, Delouvee, & Jolley, 2020;McElroy et al, 2020;Niepel, Kranz, Borgonovi, Emslander, & Greiff, 2020;Norman, Wilding, & Conner, 2020;Olagoke, Olagoke, & Hughes, 2020;Rubaltelli, Tedaldi, Orabona, & Scrimin, 2020;Shevlin et al, 2020;Williams et al, 2020), which have addressed a variety of topics including: the use theoretical models (COM-B and social cognition models) to understand and predict COVID-19 health behaviours (Gibson Miller et al, 2020;Lin et al, 2020;Norman et al, 2020), risk perception (Niepel et al, 2020;Olagoke et al, 2020), and psychological distress (Horesh et al, 2020;Lades et al, 2020;McElroy et al, 2020;Shevlin et al, 2020). presented a systematic method for rapidly responding to priority SARS-CoV-2 policy questions.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
“…Because no end to the pandemic is currently in sight, public health officials have called for the widespread adoption of preventative behaviors that can curb the spread of COVID-19. Among the most effective preventative behaviors is face mask wearing, which has been extensively supported to reduce airborne transmission of viruses ( Leung et al, 2020 ; O'Dowd et al, 2020 ); however, many people are resistant to face mask wearing despite the effectiveness of the practice, which poses extreme risks in the context of the COVID-19 pandemic ( Howard, 2020 ; Lyu & Wehby, 2020 ). These risks are exponentially heightened as more people refuse to wear face masks, because each unmasked person multiplicatively increases the likelihood of infecting each other ( Howard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%